An Application of a Negative-Pressure Wound Dressing for Partial- or Full-Thickness Burn Wounds. (September 2021) - Cheng, Yulong; Zhou, Zengding; Hu, Huan; Li, Wenbo; Liu, Yi; Xia, Zihuan; Deng, Chenliang; Mao, Guangyu; Yi, Lei; Liu, Xiangdong; Yang, Songlin; Zheng, Jianghong; et al.
Negative-pressure wound therapy is widely used in burn populations. Traditionally, negative-pressure devices use persistent vacuum suction, requiring a longer hospital stay. In this study, we applied a novel negative-pressure wound dressing for burn wounds, which eliminates the hospital stay. The medical records of 39 patients with partial-/full-thickness burns treated by negative-pressure wound dressing were retrospectively analyzed. The average burn area, burn degree, healing duration, cost, and incidents during treatment were determined and compared with previous data for conventional therapies. In conclusion, for patients diagnosed with partial-thickness or full-thickness burns and a burn area <34.6 ± 2.21 cm 2, the negative-pressure wound dressing is a reliable option, especially for burnt children. Moreover, the negative-pressure wound dressing treatment was not only much cheaper than conventional therapies, but also eliminated hospital stay in patients with small-area deep burn wounds.